2021
DOI: 10.1253/circj.cj-20-0854
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Sacubitril/Valsartan in Japanese Patients With Chronic Heart Failure and Reduced Ejection Fraction ― Results From the PARALLEL-HF Study ―

Abstract: Background: In the Prospective Comparison of angiotensin receptor neprilysin inhibitor (ARNI) With ACEi to Determine Impact on Global Mortality and Morbidity in Heart Failure (PARADIGM-HF) study, treatment with sacubitril/valsartan reduced the primary outcome of cardiovascular (CV) death and heart failure (HF) hospitalization compared with enalapril in patients with chronic HF and reduced ejection fraction (HFrEF). A prospective randomized trial was conducted to assess the efficacy and safety of sacubitril/ va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 22 publications
1
62
0
2
Order By: Relevance
“…Early and sustained reductions in NT-proBNP from baseline were observed with sacubitril/valsartan compared with enalapril (between-group difference at week 2 of 25.7% [P < .01] and at month 6 of 18.9% [P = .01], favoring sacubitril/valsartan). 60 In contrast, in the PARAGON-HF study involving patients with heart failure retaining LVEF (HFpEF) including Japanese patients, the sacubitril/valsartan group and valsartan group were compared and significant differences were not observed in the composite primary end point of total (first and recurrent) hospitalizations for heart failure and cardiovascular death. However, in a subgroup analysis specified beforehand, significant effects of sacubitril/valsartan were noted in the primary end point, female or a LVEF of 57% or less.…”
Section: Arni: Sacubitril/valsartanmentioning
confidence: 99%
See 1 more Smart Citation
“…Early and sustained reductions in NT-proBNP from baseline were observed with sacubitril/valsartan compared with enalapril (between-group difference at week 2 of 25.7% [P < .01] and at month 6 of 18.9% [P = .01], favoring sacubitril/valsartan). 60 In contrast, in the PARAGON-HF study involving patients with heart failure retaining LVEF (HFpEF) including Japanese patients, the sacubitril/valsartan group and valsartan group were compared and significant differences were not observed in the composite primary end point of total (first and recurrent) hospitalizations for heart failure and cardiovascular death. However, in a subgroup analysis specified beforehand, significant effects of sacubitril/valsartan were noted in the primary end point, female or a LVEF of 57% or less.…”
Section: Arni: Sacubitril/valsartanmentioning
confidence: 99%
“…In the PARALLEL-HF study involving Japanese, a 36-hour washout period, about 3 times longer than the elimination half-life of ACE inhibitors and LBQ657, was set, and no obvious angioedema was observed. 60 For the actual use, it is recommended to discontinue ACE inhibitor administration 36 hours before the initiation of sacubitril/valsartan administration and combination with ACE inhibitors is contraindicated. Amyloid b is known as a substrate of neprilysin.…”
Section: Arni: Sacubitril/valsartanmentioning
confidence: 99%
“…Early and sustained reductions in NT-proBNP from baseline were observed with sacubitril/valsartan compared with enalapril (betweengroup difference at week 2 of 25.7% [P<0.01] and at month 6 of 18.9% [P=0.01], favoring sacubitril/valsartan). 60 In contrast, in the PARAGON-HF study involving patients with heart failure retaining LVEF (HFpEF) including Japanese patients, the sacubitril/valsartan group and valsartan group were compared and significant differences were not observed in the composite primary end point of total (first and recurrent) hospitalizations for heart failure and cardiovascular death. However, in a subgroup analysis specified beforehand, significant effects of sacubitril/valsartan were noted in the primary end point, female or a LVEF of 57% or less.…”
Section: Arni: Sacubitril / Valsartanmentioning
confidence: 99%
“…In the PARALLEL-HF study involving Japanese, a 36-hour washout period, about 3 times longer than the elimination half-life of ACE inhibitors and LBQ657, was set, and no obvious angioedema was observed. 60 For the actual use, it is recommended to discontinue ACE inhibitor administration 36 hours before the initiation of sacubitril/ valsartan administration and combination with ACE inhibitors is contraindicated. Amyloid β is known as a substrate of neprilysin.…”
Section: Arni: Sacubitril / Valsartanmentioning
confidence: 99%
“…Among the 10 studies, one study (United Kingdom HARP-III, 414 patients, 15 of them reported heart failure) assessed CKD patients with an eGFR of 20-60 ml/min/1.73 m 2 , one study [Post-STEMI (Rezq et al, 2021), 200 patients] assessed patients after ST-segment elevation myocardial infarction. Five studies [54.9%, 10,085/ 18,362, PARADIGM (McMurray et al, 2014), PIONEER (Velazquez et al, 2019), EVALUATE (Desai et al, 2019), PRIME (Kang et al, 2019), and PARALLEL (Tsutsui et al, 2021)] assessed patients with HFrEF, while the other three…”
Section: Resultsmentioning
confidence: 99%